Revoluções tecnológicas e o catch-up da China na economia digital - Bruno Prado Prates (2022)
Different approaches confirm the existence of metamorphoses of capitalism: the occurrence in the long-term of transformations in the international division of labor, motivated by technological revolutions, which modify the center-periphery system. We discuss the emergence of the Digital Revolution, possibly born from the invention, in 1991, of the World Wide Web. This period is particularly relevant for China because, for the first time since the Industrial Revolution, the Asian country presents national companies - such as Baidu, Alibaba, Tencent, and Huawei – which directly rival companies from Western powers. The objective of this work is to investigate China's different responses to the emergence of technological revolutions, focusing on the emerging Digital Revolution and the strategies adopted by the country to perform a technological catch-up in the key technologies of this revolution. Thus, we can assess the successes achieved and the ongoing risks of the strategies adopted. As specific objectives, we list four points: i – to connect the literature on technological revolutions and the literature on the center-periphery system; ii – describe the historical formation of the current Chinese economy, highlighting its link with technological revolutions and the construction of absorption capacities; iii – evaluate the characteristics of the Digital Revolution and its reception in China; iv – discuss the catch-up strategies adopted.